Chapter Coastal dunes along the Marche littoral (Adriatic side of central Italy) - Cantalamessa, Gino (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
An analysis of the main features of relict dunes and scarcely anthropized zones located along the littoral of the Marche Region is reported. The coast is strongly affected by man-made transformations mostly implemented from the '60s of the previous century to face beach erosion triggered by a reduction of river solid load derived from man-made interventions in the hydrographic basins. Presently, no real beach-dune still exists, but, locally, some eroded remnants can be found. The typical vegetation of dunes is very fragmented, depleted and strongly altered. Standing their extremely relevant ecologic function, it is instrumental to carry out actions aiming at preserving these relic dunal areas.